2004
DOI: 10.1111/j.1464-410x.2003.04740.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of serum prostate specific antigen in childhood

Abstract: OBJECTIVE To investigate serum prostate specific antigen (PSA) levels with age and sex in childhood. SUBJECTS AND METHODS This prospective study included 205 children (123 boys, 82 girls; mean age 59.27 months, sd 3.78, range 2 days to 204 months) with no urogenital or endocrine disorders. PSA levels were measured using a highly sensitive, ‘third‐generation’ PSA (time‐resolved immunofluorometric) assay, able to detect PSA levels of ≥ 1 ng/L (0.001 ng/mL). Children were divided into four groups by age, i.e. A (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…13), the same group showed that the serum PSA (sPSA) does not differ significantly between boys and girls until 12 years of age (difference being observed in boys with the increase of sPSA due to prostatic development during puberty). Furthermore, another study (ref.…”
Section: Conflict Of Interestmentioning
confidence: 93%
See 1 more Smart Citation
“…13), the same group showed that the serum PSA (sPSA) does not differ significantly between boys and girls until 12 years of age (difference being observed in boys with the increase of sPSA due to prostatic development during puberty). Furthermore, another study (ref.…”
Section: Conflict Of Interestmentioning
confidence: 93%
“…A recent study from Antoniou et al showed that serum PSA levels do not differ significantly between the two sexes until the age of 12 years, with median values of 38.41 ng/L (range: 1-2768) and 4.059 (1-287) ng/L for boys and girls respectively. After the age of 12, serum PSA levels in boys are seen to increase sharply (13). Another study by Sato et al found that there is a gradual increase in uPSA activity from 1-4 month old infant males and boys older than 10 years of age.…”
Section: Commentsmentioning
confidence: 96%